A study on the demographic profiles,disease characteristics and one-week outcome of red-tag patients in the emergency department, Hospital Universiti Sains Malaysia - Rashdan, Rahmat (2007)
The sample size was 440 patients. Trauma patients were 23.0%, the rest were nontrauma patients (77.0%). The mean age of the population was 47.21 +/- 21.78. For trauma cases, the mean age for population of patients was 31.61 +/- 21.41 years old. 67.27% were male patients and about 95.0% were Malays. The highest number of patients was in the medical category (58.6%). Neurosurgical cases contributed to 25.0% of the total cases. Most of the trauma cases involved patients less than 60 years old (84.1 %). The mean duration of stay in ED was 3.92 +/- 1.5 hours. A total of 27 patients died. Seven (1 .59%) of them were trauma patients. There was a significant difference between the RTS value and the mortality within the period of one week (<0.05, 95% CI: -4.4,-1.0). There was also a significant difference between the SI value and the mortality within the period of one week (p<0.05, 95% CI: 0.3 - 0.8). There were no significant differences comparing the mean of age, sex, mean duration of ED stay as well as the duration of oneweek ward stay with the mortality {p>0. 05). There were also no significant differences when comparing the individual components ofRTS (GCS, RR and SBP) and SI (HR and SBP) with the mortality (p>0.05).